Psychological distress: The role of self-regulated learning in online learning during the COVID-19 pandemic - Elgeka, Honey Wahyuni Sugiharto; Pujibudojo, Jatie K. (Humanitas: Indonesian Psychological Journal, 2023)
Online learning has become a solution for the world of education, including universities, during the COVID-19 pandemic. Every student behaves differently in addressing online learning in their lives. This research aimed to explore the role of self-regulated learning on psychological distress among university students in the online learning process during the COVID-19 pandemic. Four hundred sixteen students participated online survey and completed Depression Anxiety Stress Scale – 21 and the Online Self-Regulated Questionnaire. The correlation results show that self-regulated learning negatively correlates with depression, although the level of depression is mild to moderate. Besides that, students in the third and fourth years of study found that they had a higher score of depression on online learning than the first and second years of study. Therefore, the capacity to motivate and identify the direction of self-regulated learning will make students actively participate in online learning and could adapt to online learning during the COVID-19 pandemic. Thus, more self-regulate learning relates to lower depression among students.